2018
DOI: 10.1002/ecs2.2449
|View full text |Cite
|
Sign up to set email alerts
|

Shorescape‐level factors drive distribution and condition of a salt marsh facilitator (Geukensia demissa)

Abstract: Ribbed mussels (Geukensia demissa) are a highly abundant bivalve filter feeder throughout the salt marshes of the U.S. Atlantic Coast. These mussels form a mutualistic relationship with smooth cordgrass Spartina alterniflora wherein the grass provides habitat and shade to the mussels, and the mussels stabilize the sediment and fertilize the grass. Salt marshes are, however, rapidly changing and eroding as humans modify the coast, and the rate of sea level rise is accelerating. In order to understand how ribbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Ribbed mussels have a mutualistic relationship with cordgrass (Angelini et al 2016, Bilkovic et al 2017 b ) and higher densities of this marsh plant are correlated with mussel density (Bertness 1984, Honig et al 2015, Isdell et al 2018). We also observed this pattern for both living shorelines and paired reference marshes when mussels were present at our sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ribbed mussels have a mutualistic relationship with cordgrass (Angelini et al 2016, Bilkovic et al 2017 b ) and higher densities of this marsh plant are correlated with mussel density (Bertness 1984, Honig et al 2015, Isdell et al 2018). We also observed this pattern for both living shorelines and paired reference marshes when mussels were present at our sites.…”
Section: Discussionmentioning
confidence: 99%
“…Within the low marsh (cordgrass dominated) area, we placed two 0.25 m 2 quadrats along each transect at 1‐m intervals representing distances of 0–1 and 1–2 m from the seaward edge and we counted the number of adult and juvenile (<25 mm) mussels and cordgrass stems in each quadrat. Previous work within Chesapeake Bay marshes has shown that the vast majority of mussels (~85%) are found within 2 m of the seaward edge (Bilkovic et al 2017, Isdell et al 2018). We averaged mussel densities across all quadrats ( N = 12) for a given site and compared marsh types using paired t ‐tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecological studies have consistently found that shoreline armoring negatively impacts the intertidal and nearshore benthic and nekton communities relative to unmodified sections of shoreline via habitat fragmentation (Peterson & Lowe, 2009), changes in nearshore erosion processes (Bozek & Burdick, 2005), increased depth of nearby waters (Toft et al, 2013), reduced species abundance and diversity (Bilkovic et al, 2006;Bilkovic & Roggero, 2008;Kornis et al, 2017;Seitz et al, 2006) at both local and landscape scales (Isdell et al, 2015), and prevention of landward migration of intertidal habitats (Bilkovic, 2011;Titus et al, 2009). The ecological and social benefits of coastal wetlands (e.g., Mitsch & Gosselink, 2015) typically center around storm surge protection (Spalding et al, 2014;Shephard & Grimes, 1983), water quality enhancement (Bilkovic et al, 2017a;Erwin, 2009;Nelson & Zavaleta, 2012;Zedler & Kercher, 2005), habitat provision (Angelini et al, 2015;Isdell, Bilkovic & Hershner, 2018;Rozas & Minello, 1998), and carbon sequestration (Davis et al, 2015;Mcleod et al, 2011). Owing to the extensive ecosystem services provided by natural marshes and the unique challenges to protect coastal communities under changing conditions while supporting nearshore and intertidal ecosystems, nature-based shoreline protection is the preferred alternative to shoreline armoring where suitable.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in the local distribution across their range may be a result of variability in tidal heights, which can range from as low as 0.12 m in Maryland to as high as 3 m in the state of Georgia (Stiven and Gardner 1992), and the associated elevation gradients in these marshes. While previous studies have focused on factors that may influence ribbed mussel distribution throughout their range, typically focusing on factors at fine scales, such as vegetation type/density (Keunzler 1961;Watts et al 2011;Schalles et al 2013;Honig et al 2015) and distance to marsh edge (Lin 1989;Stiven and Gardner 1992;Nielson and Franz 1995), more recent studies have considered both fine-and broad-spatial scale factors (Isdell et al 2018;Julien et al 2019;, although these recent studies usually only examined two or three factors (but see .…”
Section: Introductionmentioning
confidence: 99%